Performance comparison of distributed generation installation arrangement in transmission system for loss control - Shaaya S.A.; Musirin I.; Sulaiman S.I.; Mansor M.H.; Syed Mustaffa S.A. (Institute of Advanced Engineering and Science, 2023)
Placing Distributed generation (DG) into a power network should be planned wisely. In this paper, the comparison of having different installation arrangement of real-power DGs in transmission system for loss control is presented. Immune-brainstorm-evolutionary programme (IBSEP) was chosen as the optimization technique. It is found that optimizing fixed-size DGs locations gives the highest loss reduction percentage. Apart from that, scattered small-sized DGs throughout a network minimizes transmission loss more than allocating one biger-sized DG at a location. 2019 Institute of Advanced Engineering and Science.